Internalization of Religious Values for Elementary-Age Children in Integrated Islamic Elementary School - Mahariah Mahariah (AL-ISHLAH: Jurnal Pendidikan, 2023)
Elementary-age children are the "reflection of Indonesia" of the future. This age phase is the generation of Indonesian human resources (HR) at the golden age of 1 century of independence. Not only intellectually, but children of primary age are also expected to have skills and character, including religious values. This paper aims to analyze the internalization of religious values for elementary-age children with a research background at Islamic elementary school at Biak Muli Kutacane, Aceh Tenggara. This research uses a qualitative approach with a case study method. The data were collected by using interviews, observation and documentation techniques. Furthermore, data analysis was carried out using data reduction techniques, data display and drawing conclusions. The data validity test used the triangulation technique. The results of this study indicate that the internalization of religious values for elementary-age children at Islamic elementary school is classified into 3 (three) parts, namely Tahfiz Alquran, Clothing, and Religious.